(untitled) (Bangladesh Journal of Agricultural Research, 2010)
A survey was conducted to assess the postharvest practices and lossess of litchi during May to June 2008. Three litchi growing areas viz., Dinajpur, Ishurdi, and Natore, two urban areas, namely, Dhaka and Gazipur were selected for this study. Some indigenous postharvest practices were observed to follow in all the growing areas mostly by the growers and/or beparies those are involved in harvesting. These practices were as pre-cooling by keeping the harvested fruits under the shade of the trees, sorting based on damaged, pest infested, and disease infected fruits and so called believed cooling with litchi leaves during transportation. Nobody practices the grading of fruits. The usual packaging practices were observed mainly with bamboo baskets lining with litchi leaves and covering with gunny sheets. None of the aradthdars involved in packaging .The postharvest losses were reported mainly at harvesting (8.0%), handling from orchard to selling point by the growers and beparies involved in harvesting (4.61%) and after buying to consumption by the consumers (7.5%). Considering the channels involved in litchi marketing, the growers and/or beparies engaged in harvesting had the highest percent of losses (16% in Dinajpur, 12% in Ishurdi, and 11 % in Natore) followed by the consumers (7.5%). Keywords: Litchi; harvesting practices; mode of packaging and transportation and postharvest losses. DOI: 10.3329/bjar.v35i3.6451 Bangladesh J. Agril. Res. 35(3) : 439-451